Egg characteristics of Japanese quail fed diets containing guava extract (Psidium guajava L.) - Oliveira, Helder Freitas de; Leandro, Nadja Susana Mogyca; Mascarenhas, Alessandra Gimenez; Carvalho, Deborah Pereira; Mendonça, Raiana Almeida Noleto; Oliveira, Natiele Ferraz de; Pereira, Ligia Sarneiro; Mello, Heloisa Helena de Carvalho (Acta Scientiarum. Animal Sciences, 2021)
The main purpose of this study was to evaluate the characteristics of eggs produced by Japanese quails fed with guava extract. A total of 400 eggs collected from the quails fed with experimental diets, were distributed in a completely randomized design in factorial arrangement 4 x 4 with main effects including four dietary levels of guava extract (0, 3, 6 and 9 g kg-1) and four storage periods (0, 9, 18 and 27 days) totalizing 16 treatments with five replicates of five eggs. The eggs were produced by Japanese quails, fed with experimental diets. The diets were isonutritive formulated by corn-soybean basis. The eggs were stored for different periods, at the same conditions, to constitute the treatments. The parameters evaluated were egg weight loss (g and %), yolk color, Haugh unit, specific gravity, eggshell thickness and pH of the yolk and albumen. Data were submitted to ANOVA, and means were compared using Scott-Knott test, using α = 0.05. The specific gravity of fresh eggs was better with the use of 6 g kg-1 of guava extract in the diet. The use of 3 g kg-1 of guava extract resulted in smaller eggshell thickness of fresh eggs. The Haugh unit was affected just by the storage periods. The dietary guava extract (3, 6 or 9 g kg-1) increased the pH of albumen in eggs stored for 27 days. The use of 6 g kg-1 of guava extract in quails diet increase the specific gravity in fresh eggs and increase the yolk color when the eggs are stored.